2021
DOI: 10.3389/fbioe.2021.641372
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Like Aggregation in Diseases and Biomaterials: Osmosis of Structural Information

Abstract: The discovery that the polypeptide chain has a remarkable and intrinsic propensity to form amyloid-like aggregates endowed with an extraordinary stability is one of the most relevant breakthroughs of the last decades in both protein/peptide chemistry and structural biology. This observation has fundamental implications, as the formation of these assemblies is systematically associated with the insurgence of severe neurodegenerative diseases. Although the ability of proteins to form aggregates rich in cross-β s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 263 publications
(288 reference statements)
0
36
0
Order By: Relevance
“…Moreover, it was found that significant portions of proteins are intrinsically disordered, and operate dynamically [ 19 ]. Finally, it has been shown that polypeptide chains have an intrinsic and unexpectedly strong propensity to self-assemble in misfolded states in which they assume a cross-β structure that is characteristic of amyloid aggregates [ 20 , 21 ]. In this scenario, here we performed a comparative biophysical characterization of the three members of the GADD45 protein family that are involved in a myriad of diversified biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that significant portions of proteins are intrinsically disordered, and operate dynamically [ 19 ]. Finally, it has been shown that polypeptide chains have an intrinsic and unexpectedly strong propensity to self-assemble in misfolded states in which they assume a cross-β structure that is characteristic of amyloid aggregates [ 20 , 21 ]. In this scenario, here we performed a comparative biophysical characterization of the three members of the GADD45 protein family that are involved in a myriad of diversified biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The specific three-dimensional structure depends on the different connection modes between peptides, including hydrogen bonding, electrostatic force hydrophobicity, and π-π interaction. In addition, β-rich structures provided important information for self-assembling peptides [34].…”
Section: Composition Of Sap Supramoleculesmentioning
confidence: 99%
“…These attractive properties of amyloid fibrils have inspired the development of various artificial materials for applications in sensors [ 31 ], medicines [ 32 , 33 ], fabrics [ 34 , 35 ], and other functional materials [ 36 , 37 , 38 ]. The use of amyloid in nanomaterials has been extensively reviewed previously [ 20 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. This review focuses on recent advances in engineering amyloids peptides or proteins as functional materials in macroscopic scales.…”
Section: Introductionmentioning
confidence: 99%